1968
DOI: 10.1002/app.1968.070120613
|View full text |Cite
|
Sign up to set email alerts
|

ESR study of reactions of cellulose with ·OH generated by Fe+2/H2O2

Abstract: SynopsisIt was demonstrated by ESR spectroscopy that the Fe+2/Hz0z syst,em gave a reactive species which generated an ESR triplet spectrum or sorbitol similar to that generated by hydroxyl radicals from the Ti+3/Ha03 system. An ESR spectrum was obtained for the hydroxyl radicals generated by the latter system. However, the lifetime of hydroxyl radicals, generated by the Fe+2/Hz0z system, was apparently very short, and an ESR spectrum for the hydroxyl radicals, generated by this system, was not observed. The Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…ESR studies of the reaction of cellulose with hydroxy radicals generated by Fe 2+ -H202 in a flow system, have been described by Arthur et al 76 ). It has been suggested, considering ESR spectrum shown in Figure 5.86, that hydrogen atoms 5.…”
Section: Reactions Of Polymers With Hydroxy Radicalsmentioning
confidence: 99%
“…ESR studies of the reaction of cellulose with hydroxy radicals generated by Fe 2+ -H202 in a flow system, have been described by Arthur et al 76 ). It has been suggested, considering ESR spectrum shown in Figure 5.86, that hydrogen atoms 5.…”
Section: Reactions Of Polymers With Hydroxy Radicalsmentioning
confidence: 99%
“…; droxyl radicals, in a separate reaction, for example, in the ferrous ion-hydrogen peroxide system, which . abstract hydrogen atoms from cellulose to leave freeradical sites on the cellulose molecule [ 14 ] . _ Using electron spin resonance (ESR) spectroscopy, we have investigated these methods and the copolymerization reactions of the activated celluloses with acrylonitrile.…”
Section: Graft Copolymerization Reactionsmentioning
confidence: 99%
“…reaction when the free-radical sites were formed. Analyses of ESR spectra indicated that with ceric ions the radicals were likely formed at carbon C2 arid/or Cs and that with ferrous ion-hydrogen peroxide the radicals were likely formed at carbon C6 and/or C6 [2,14] . Also, in using methods VI and VII, it was likely that the free-radical sites were formed in the less ordered areas of the cotton fiber.…”
Section: Graft Copolymerization Reactionsmentioning
confidence: 99%
See 2 more Smart Citations